agriculture, fisheries, forestry, West Kutai, zone - Wulandari, Indah; Irawan Wijaya, Harlinda Kuspradini, (Agrifor : Jurnal Ilmu Pertanian dan Kehutanan, 2018)
Litsea is a important genus from Lauraceae family, found in the tropic and subtropic Asia, Australia and from North to South America. Related literature review with biology activity show that secondary metabolite compounds in the Lauraceae plants contained insecticide and cytotoxic activities. Insecticide activities show bioactive compounds such as alkaloid, terpenoid and flavonoid. Botanical insecticides by terpenoid groups that found is piretrin, camphene and azardirakhtin. This research do to analyze secondary metabolite compunds by five species Litsea extract from bole, bark and leaf. Analysis of phytochemical compunds using qualitative method. Based on test result can be known that five species positively contains alkaloids, flavonoids, tannins, carbohydrate and coumarins.